The Hong Kong national security law: A harbinger of China's emerging international legal discourse power - Moritz Rudolf (Stiftung Wissenschaft und Politik (SWP), 2020)
The Law of the People's Republic of China on Safeguarding National Security in the Hong Kong Special Administrative Region (Security Law) highlights the shortcomings of the 1984 Sino-British Joint Declaration and the inherent conflicts of the 'one country, two systems' principle. The arrangement has always been full of contradictions and grey areas. With the Security Law, the Chinese leadership has created facts on the ground. The move comes at the expense of civil liberties and accelerates the spread of socialist legal concepts in Hong Kong. But, on this issue, Beijing is not isolated internationally. On the contrary, it is supported by economically dependent states in its assessment of the Security Law as an internal affair. China's ambition to gain international discourse power in legal matters is strategically embedded in the Belt and Road Initiative (BRI). Beijing's course of action in Hong Kong serves as a test balloon in this endeavour. Decision-makers in Germany and Europe are still not sufficiently aware of the problems concerning Chinese legal concepts. More expertise is urgently needed.
Keywords: 320